When things cast no shadow. - Szymczyk, Adam; Filipovic, Elena; KW Institute for contemporary art, Berlin (Berlin : KW - Institute for Contemporary Art, 2008)
Auder, Michel ; Bodzianowski, Cezary ; De Boer, Manon ; De Gruyter, Jos ; Thys, Harald ; Esquivias, Patricia ; Guzman, Daniel ; Hwan Kim, Sung ; Maljkovic, David ; Mangolte, Babette ; Mishori, Jacob ; Molska, Ania ; Ogut, Ahmet ; Piscitelli, Giulia ; Pushwagner ; Reynaud-Dewar, Lili ; Seda, Katerina ; Thater, Stefan ; etc.
05.04.2008 - 15.06.2008
2 Volumes : When things cast no shadow : Day / When things cast no shadow : Night
boek